Pharmacognostical and preliminary phytochemical screening of the corm of Stephania hernandifolia (Willd.) Walp. - Sharma, Uttam; Nandi, R. P. (Journal of Applied Pharmaceutical Research, 2013)
The aim of the study is to cover the pharmacognostical and preliminary phytochemical screening of the corm of Stephania hernandifolia (Willd.) Walp. Stephania hernandifolia (Willd.) Walp. belonging to the family Menispermaceae is a natural taxon. The plant was collected from the Darjeeling district of West Bengal, India, during summer and was authenticated by the botanist. Pharmacognostical study included macroscopical characters, microscopical characters, physico-chemical constants and fluorescence analysis. Preliminary phytochemical screening includes phytochemical extraction, phytochemical testing and thin layer chromatography (TLC). In macroscopical studies of the corm, it was found that, itâs shape was spherical, size was about 8 to 20 cm in length and 10 to 20 cm broad, colour was brown (Rusty), surface was rough, odour was not specific, taste was bitter, direction of growth was vertical, the surface has many circular and slightly raised spots. In microscopical studies of corm, it were found that it has periderm, vascular bundles, thin phelloderm cells, ground parenchymatous cells, dense masses of starch grains and wide circular secretory cavities were seen. In powder microscopy, sclereids and vessel elements have been observed with short sclerenchyma. Physico-chemical parameters like total ash value (13 % w/w), acid insoluble ash value (2.66 %w/w), water-soluble ash value (2.50 %w/w) and sulphated ash value (3.33 %w/w) were observed. Alcohol soluble extractive value (7.23 %w/w), water-soluble extractive value (10.84 %w/w) were also observed and loss on drying was observed as 2.50 %w/w. The foaming index was found to be 111.11. Preliminary phytochemical studies show the presence of alkaloids, carbohydrates, Steroids, Saponin, tannin and phenolic compounds flavanoids, and lignin in ethanolic extract and carbohydrates, Saponin, tannin and phenolic compounds flavanoids, and lignin in aqueous extract. Performing TLC of ethanolic extract using chloroform: ethanol (30:70) and methanol: water (70: 30) as solvent system, few spots were identified. The study helps in the correct identification of the plant. The presence of alkaloids and flavanoids explains that the plant must have valuable medicinal properties which must be explored.